Improvement of a Rapid Screening Test for Chronic Granulomatous Disease. (July 2013) - Iacobini, M.; Duse, M.; Di Coste, A.; Balducci, L.
Diagnosis of CGD is made by demonstrating absent or markedly reduced oxidase activity in stimulated neutrophils. The screening test proposed is based upon the naked eye evaluation of the reduction of NBT on a solid surface. It seems to be a useful tool for rapid and inexpensive detection of CGD patients, especially for large-scale screening purposes. The test was carried out on forty-five subjects: two males affected by CGD, three female carriers and forty healthy donors. The test confirmed the results obtained with flow cytometric and NBT assays.